2017
DOI: 10.1245/s10434-017-5833-3
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Multidisciplinary Team Meetings for Patients with Gastrointestinal Malignancies: A Systematic Review

Abstract: IntroductionThe incidence of gastrointestinal (GI) cancer is rising and most patients with GI malignancies are discussed by a multidisciplinary team (MDT). We performed a systematic review to assess whether MDTs for patients with GI malignancies can correctly change diagnosis, tumor stage and subsequent treatment plan, and whether the treatment plan was implemented.MethodsWe performed a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 32 publications
3
79
0
9
Order By: Relevance
“…Our results also demonstrate that MTP is associated with improvements in timeliness, surgical technique, and survival, although statistically significant effects were not consistently observed. Our findings are comparable to those reported when MTP effectiveness was evaluated in health systems in other countries and align with the conclusions of reviews that addressed MTP only in the context of a single disease site or MTP outcome . Taken together, these results add to the body evidence supporting MTP as a critical element in US standards of cancer care…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results also demonstrate that MTP is associated with improvements in timeliness, surgical technique, and survival, although statistically significant effects were not consistently observed. Our findings are comparable to those reported when MTP effectiveness was evaluated in health systems in other countries and align with the conclusions of reviews that addressed MTP only in the context of a single disease site or MTP outcome . Taken together, these results add to the body evidence supporting MTP as a critical element in US standards of cancer care…”
Section: Discussionsupporting
confidence: 87%
“…Only 2 studies addressed cost. Although MTP is relatively inexpensive and reduces expenditures during diagnosis/staging, 2 recent systematic reviews concluded that evidence of MTP cost effectiveness remains sparse. Second, comorbidities and palliative care were rarely incorporated into MTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies included in each review varied, ranging from 16 to 51 studies. Sixteen studies were included in the systematic review focused on lung cancer [33]; 16 in the review concerning gastrointestinal cancers [34]; and 51 [31], 27 [32] and 37 [30] studies were included in the other 3 reviews. Some of the articles included were found in two or more of the reviews considered.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the articles included were found in two or more of the reviews considered. More precisely, one study was cited in four out of five reviews [30][31][32]34] and three studies were shared by three reviews (one study in common by Prades [31], Pillay [32] and Basta [34]; one by Prades [31], Pillay [32] and Lamb [30] and one by Pillay [32], Basta [34] and Lamb [30]). Other primary studies were common to two reviews.…”
Section: Resultsmentioning
confidence: 99%